The Effectiveness of an Ethno-ESD-Based Science Textbook in Improving Environmental Literacy and Critical Thinking Skills of Junior High School Students on the Topic of Climate Change - Okky Ratri; Sudarmin Sudarmin; Bambang Subali (Universitas Negeri Semarang, 2026)
Climate change requires educational approaches that enhance students’ scientific understanding while developing sustainability competencies and higher-order thinking skills, yet integrating Education for Sustainable Development (ESD) with local wisdom into a single, contextualized resource for junior high school climate change education remains rarely examined. This study investigated the effectiveness of an Ethno-Education for Sustainable Development (Ethno-ESD)-based Science Textbook in improving junior high school students’ environmental literacy and critical thinking skills on the topic of climate change. A quantitative, quasi-experimental design with a non-equivalent control group pretest-posttest design was used. Two intact junior high school classes participated: an experimental class taught using the Ethno-ESD-based Science Textbook and a control class taught using the conventional textbook. Data were collected through environmental literacy and critical thinking tests, analyzed using N-Gain analysis, the Independent Samples t-test, and Cohen’s d. The experimental class showed greater improvement in environmental literacy (N-Gain = 0.63) and critical thinking skills (N-Gain = 0.62) than the control class (N-Gain = 0.31 for both), with statistically significant differences (t = 5.873 and 6.142, p < 0.05) and large effect sizes (Cohen’s d = 0.88 and 0.92, respectively). Integrating ESD principles, climate change education, and local wisdom created meaningful, contextual learning that strengthened students’ sustainability competencies and higher-order thinking. The Ethno-ESD-based Science Textbook is therefore an effective, innovative resource for promoting environmental literacy and critical thinking in junior high school science learning, offering a transferable model for other culturally diverse settings.